Implementation Of The Witness And Victim Protection Act For Victims Of Personal Data Theft Crimes - Permana, Gabriel Riziq; Harmono , Harmono (Asian Journal of Social and Humanities, 2025)
The rapid development of information technology in Indonesia also increases the risk of personal data theft through digital media. This research aims to analyze the effectiveness of legal protection for victims of personal data theft based on the legal framework applicable in Indonesia, and compare it with data protection systems in other countries. The method used is normative juridical with conceptual and comparative approaches. The results show that legal protection for victims in Indonesia still faces serious challenges, especially related to weak law enforcement, limited supervisory institutions, and not optimal recovery mechanisms. Data leakage cases that occurred throughout 2025, such as incidents on digital financial and health service platforms, show that victims' rights have not been fully protected effectively. In comparison, regulations such as GDPR in the European Union and PDPA in Singapore show a more proactive and pro-user system. Therefore, it is necessary to strengthen national policies through the enactment and implementation of the Personal Data Protection Law, increase the capacity of law enforcement, and synergize across sectors to create a safe and equitable digital ecosystem.